Four Dimensional Gravity Forward Model in a Deep Reservoir - Mancinelli, Paolo (Frontiers in Earth Science, 2020)
In this work, we calculate the gravity signature of small density changes in a real-case deep reservoir. Based on the 3D forward density modeling of constrained geometries and using parameters of the involved rocks and fluids, we compute the differential gravity signature before and after the production period of the Volve oil field in the North Sea. Causative sources of the retrieved residuals are spatially correlated with positions of the most productive wells, locating areas of maximum density change. Results show that the 4D gravity forward model is capable of resolving residual gravity signatures also for deep and small density changes. In particular, we locate ∼−13 μGal gravity minima over the 2750 m deep reservoir; this minima was caused by the −53 kg m–3 density change related to production and injection activity.